Answer:
The simplest form of the given expression
[tex]3(2x+y)+4(x-4y)+x^2[/tex] is [tex]x^2+10x-13y[/tex]
Step-by-step explanation:
Given expression is [tex]3(2x+y)+4(x-4y)+x^2[/tex]
To find the simplest form of the given expression :
[tex]3(2x+y)+4(x-4y)+x^2[/tex]
[tex]=6x+3y+4x-16y+x^2[/tex] ( By using the distributive property )
[tex]=6x+4x+3y-16y+x^2[/tex] (combine the like terms )
[tex]=10x-13y+x^2[/tex] ( Adding the like terms )
Rewritting the above equation as below
[tex]=x^2+10x-13y[/tex]
Therefore [tex]3(2x+y)+4(x-4y)+x^2=x^2+10x-13y[/tex]
Therefore the simplest form of the given expression
[tex]3(2x+y)+4(x-4y)+x^2[/tex] is [tex]x^2+10x-13y[/tex]